ON THE ESTIMATION OF THE PRECIPITATION RATE AT EACH ALTITUDE BY A NEW ANALYTICAL METHOD FOR THE METEOROLOGICAL RADAR ECHO (5) - ハタナカ, マサヒコ; キムラ, シンウ; ヨシダ, ユタカ; ワダ, マコト; ヒラサワ, ナオヒコ; HATANAKA, Masahiko; KIMURA, Shinya; YOSHIDA, Yutaka; WADA, Makoto; HIRASAWA, Naohiko (National Institute of Polar Research, 1996)
P(論文) Using the echo data of vertical pointing meteorological radar and the snow particle size distributions observed on the ground at Syowa Station, Antarctica, the precipitation rate at each altitude was estimated (H. TAKEYA et al.; Proc. NIPR Symp. Polar Meteorol. Glaciol., 8,169,1994). But the particle size distribution at each altitude is probably different from that on the ground. We estimated the precipitation rate at each altitude based on an empirically determined distribution model (J. AWAKA et al.; J. Radio Res. Lab., 32,73,1985). Since snow particle size distribution depends strongly on the temperatures in this model, the distribution at each altitude is determined by that on the ground and the atmospheric temperature profile measured by radiosonde. At higher altitude, the sizes of snow particles tend to decrease, the back scattering cross sections and reflectivities decrease, and the values of estimated precipitation rate increase. Our preliminarily results showed that the differences between the estimated precipitation rates by TAKEYA et al. and those in this study become about 20% at altitude 1000m. departmental bulletin paper